The Correlation Between Interest, Motivation, English Self-Concept and English Speaking Performance in Nursing Students - Apriliyanti, Retno; Warsono, Warsono; Mujiyanto, Januarius (English Education Journal, 2018)
Individual differences become the main problem for learners in developing their English skills especially speaking. The identification of interest is needed to know how far students’ impression in learning English and how serious they are in continuing their progress to get their motivation. After getting along with motivation, students are expected to build up their English Self-concept, therefore English become their custom and their obstacles in learning English can be minimized. This research was to know the relationship between Interest, Motivation, English Self-concept and Speaking English Performance of Fourth Semester Nursing Students at Karya Husada Health and Science College of Semarang. This research was correlation quantitative research with cross sectional approach. The samples of this research were fourth semester of nursing students at Karya Husada Health Science College of Semarang with the numbers were 93 students by using convenience or accidental sampling technique. The data was taken by using questionnaires. The data analysis used regression to know the correlation among all variables. The result shows the correlation between interest and English speaking performance is 0.000, motivation and English speaking performance is 0.006, English self-concept and English speaking performance is 0.18 with p value <0.05, it means there is correlation between interest, motivation, English self-concept and English speaking performance. This result can contribute in teaching and learning process, it is better to conduct the investigation of individual difference in the beginning of the semester because teacher can consider the teaching method, strategies and approach well.